The importance of the region of origin effect and its implication for marketers: A qualitative research study in the Bakery Industry in Swabia - Herrmann, Johannes (2010)
Organisations are constantly focusing on creating and maintaining a competitive advantage over their competitors which cannot be copied. Therefore it is no surprise that organisations aim to use their origins to differentiate them from the competition. Origins of products, to signalise a superior product, has been used since ancient Greek (Nevett and Nevett 1994) and is still used today by marketers. This study aims to combine previous literature of country-of-origin as well as of region-of-origin with the findings of the study, to identify whether bakeries in Swabia should exploit the origin effect. The study will cross-compare three Swabian bakeries against each other and then compare these findings against the buying behaviour of Swabian consumers. The results clearly show that the organisations underestimate the region-of-origin effect. The region-of-origin effect discovered in the study is not as influential as previous findings suggest, however an especially designed strategy for any of the three bakeries may possible create a competitive advantage that is hard to be copied. However, the bakeries must first understand their consumers and only then it is possible to fully exploit the region-of-origin effect. The qualitative study employed, created limitations such as a small sample size and might not represent a ‘true’ representation of the region-of-origin effect in Swabia. However, the study still intends to provoke further research and to recommend strategies for organisation that may wish to exploit this phenomenon.